A new factor theorem for generalized absolute Riesz summability - Karakaş, A. (Carpathian Mathematical Publications, 2019)
The aim of this paper is to consider an absolute summability method and generalize a theorem concerning |N,p_n|_k summability of infinite series to φ-N,p_n;δ_k summability of infinite series by using almost increasing sequence. Furthermore, it is explained that a well known result dealing with |N,p_n|_k summability is obtained when this generalization is restricted under special conditions.